2021
DOI: 10.1016/j.scs.2021.103300
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder based weights of new sustainability indicators providing pandemic resilience for residential buildings

Abstract: During COVID-19, the building and service characteristics of residential buildings turned out to be more critical due to lockdowns. The present research assesses the importance of new sustainability indicators for residential buildings in three categories (e.g., Health and Safety, Environmental Resources Consumption, and Comfort) that provide resilience for pandemic periods. The opinions of stakeholders on the identified indicators were collected and then analyzed. ‘Health and Safety’ category is found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 60 publications
(77 reference statements)
1
23
0
Order By: Relevance
“…Due to global lockdowns, building facility features are becoming more important, as residences start playing more roles in their residents' life as not only living, but also a working and a studying place [28,29]. Nevertheless, in the light of recent pandemics, these values might change to the deterrence of virus spread, the benefit to psychological health of the occupants, and the good air qualitythose are becoming more important characteristics to the buildings [28,29]. Some of our previous works include assessment of green building certification and/or rating systems, where it has been defined that these assessment methods are not fully ready to provide sustainable requirements for buildings during pandemics [29,30].…”
Section: Influencing Factors For Performance Of Remote Education and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to global lockdowns, building facility features are becoming more important, as residences start playing more roles in their residents' life as not only living, but also a working and a studying place [28,29]. Nevertheless, in the light of recent pandemics, these values might change to the deterrence of virus spread, the benefit to psychological health of the occupants, and the good air qualitythose are becoming more important characteristics to the buildings [28,29]. Some of our previous works include assessment of green building certification and/or rating systems, where it has been defined that these assessment methods are not fully ready to provide sustainable requirements for buildings during pandemics [29,30].…”
Section: Influencing Factors For Performance Of Remote Education and ...mentioning
confidence: 99%
“…For example, in our previous works, rapid sustainability assessment methods for the Kazakhstani construction sector have been developed [ 26 , 27 ]. Due to global lockdowns, building facility features are becoming more important, as residences start playing more roles in their residents’ life as not only living but also a working and a studying place [ 28 , 29 ]. Nevertheless, in the light of recent pandemics, these values might change to the deterrence of virus spread, the benefit to the psychological health of the occupants, and the good air quality – those are becoming more important characteristics to the buildings [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health and safety in residential environments in the context of pandemics includes physical well-being, mental health, and protection from the viral transmission. Prevention of virus propagation and mental health were considered crucial characteristics of buildings during pandemics by the experts of medicine, academia, and industry [ 35 ]. Safety from virus propagation measures includes the use of new smart/innovative technologies that minimize personal involvement (e.g., touchless technologies, motion sensors, keycard swiping), self-cleaning spaces, and proper selection of indoor materials that do not facilitate viral and bacterial propagation and their increase in quantity [ [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, local services include the availability of self-dependent services in residential complexes, especially for medicine and food [91], and urban/community farming to reduce the paths for food supply and enhance mental health [92]. Based on the aforementioned sustainability indicators, expert groups from academia, industry, and medicine were surveyed in 17 countries [93], and the results showed that health and safety have the highest importance, with more attention paid to the prevention of virus propagation, mental health, and air quality. Additionally, the experts agreed that touchless technologies, self-cleaning spaces, and smart technologies contribute to avoiding the spread of viruses.…”
Section: Sustainability Indicatorsmentioning
confidence: 99%